m6A Methyltransferase METTL3 Promotes the Progression of Primary Acral Melanoma via Mediating TXNDC5 Methylation - Yue, Zhanghui; Cao, Meng; Hong, Anlan; Zhang, Qian; Zhang, Guoqiang; Jin, Zhibin; Zhao, Liang; Wang, Qiang; Fang, Fang; Wang, Yan; Sun, Jianfang (Frontiers in Oncology, 2022)
m6A modification is one of the most important post-transcriptional modifications in RNA and plays an important role in promoting translation or decay of RNAs. The role of m6A modifications has been highlighted by increasing evidences in various cancers, which, however, is rarely explored in melanoma. Here we demonstrated m6A level was highly elevated in melanoma tissues, along with the expression of METTL3, one of the most important m6A methyltransferase. Besides, higher expression of METTL3 correlated with advanced stage in melanoma patients. Knockdown of METTL3 decreased global m6A level in melanoma cells. Further, METTL3 knockdown suppressed the proliferation, migration, and invasion of melanoma cells. In METTL3 knockdown xenograft mouse models, we observed decreased volumes and weights of melanoma tissues. Mechanistically, we found that METTL3 regulate certain m6A-methylated transcripts, Thioredoxin domain containing protein 5 (TXNDC5), with the confirmation of RNA-seq, MeRIP-seq, and western blot. These data suggest that METTL3 may play a key role in melanoma and targeting the m6A dependent-METTL3 signaling pathway may be a promising strategy for the treatment of melanoma.